Duration of Tuber Dormancy in Yam Dioscorea rotundata: Effect of Plant Growth Regulators and its Relationship with Tuber Age - Hamadina, Elsie (JOURNAL OF ADVANCES IN BIOLOGY, 2015)
This study seeks to determine the effect of tuber age and plant growth regulators (PGRs) on the duration of D. rotundata tuber dormancy. Tubers of D. rotundata var. Tdr131, generated from pot grown tissue culture plantlets, were harvested at 75 days after planting (DAP) and at 179 DAP. A set of 30 tubers (untreated control) were observed for date of sprouting. Sets of ten tubers were subjected to one of nine treatments: water (treated control), two concentrations each of 2-chloroethanol (CLE), giberrellic acid (GA3) and CLE/thiourea combinations, and one concentration each of thiourea and ethephon at 183, 214, 269 and 331 DAP. The 50th percentile duration from harvest to sprouting ranged from 152 to 166 d in all controls, and 146 to 184 d in the PGR treatments (corresponding to 26 March and 12 May) depending on PGR. Tuber age at PGR application did not affect the duration from harvest to sprouting but the ethylene analogues: 60Â mlÂ l-1 CLE + 20 g l-1 thiourea and 1000 mg l -1ethephon shortened it by 32 d while 1000 mg l-1 GA3 prolonged it by 24 d.